Larvicidal study of tetrahydropyrimidine scaffolds against Anopheles arabiensis and structural insight by single crystal X-ray studies - Bairagi, Keshab M. (2018)
A series of methyl or ethyl 4-(substitutedphenyl/pyridyl)-6-methyl-2-oxo/thioxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (HPM) analogues 4a–g were synthesized and evaluated for larvicidal activity against Anopheles arabiensis. These newly synthesized compounds were characterized by spectral studies such as FT-IR, NMR (1H and 13C), LC-MS, and elemental analysis. The conformational features and supramolecular assembly of molecules 4a, 4b, and 4e were further analyzed from single crystal X-ray study. The larvicidal activity of these tetrahydropyrimidine pharmacophore series was analyzed based on their relative substituents. Among the synthesized HPM analogous from the series, compounds 4d and 4e both having electron withdrawing chlorine group on phenyl ring at the fourth position of the tetrahydropyrimidine pharmacophore exhibited the most promising larvicidal activity.